Pigment structure in the violaxanthin-chlorophyll-a-binding protein VCP - Llansola-Portoles, Manuel J; Litvin, Radek; Ilioaia, Cristian; Pascal, Andrew A; Bina, David; Robert, Bruno (Photosynthesis research, 2017)
Resonance Raman spectroscopy was used to evaluate pigment-binding site properties in the violaxanthin-chlorophyll-a-binding protein (VCP) from Nannochloropsis oceanica. The pigments bound to this antenna protein are chlorophyll-a, violaxanthin, and vaucheriaxanthin. The molecular structures of bound Chl-a molecules are discussed with respect to those of the plant antenna proteins LHCII and CP29, the crystal structures of which are known. We show that three populations of carotenoid molecules are bound by VCP, each of which is in an all-trans configuration. We assign the lower-energy absorption transition of each of these as follows. One violaxanthin population absorbs at 485 nm, while the second population is red-shifted and absorbs at 503 nm. The vaucheriaxanthin population absorbs at 525 nm, a position red-shifted by 2138 cm-1 as compared to isolated vaucheriaxanthin in n-hexane. The red-shifted violaxanthin is slightly less planar than the blue-absorbing one, as observed for the two central luteins in LHCII, and we suggest that these violaxanthins occupy the two equivalent binding sites in VCP at the centre of the cross-brace. The presence of a highly red-shifted vaucheriaxanthin in VCP is reminiscent of the situation of FCP, in which (even more) highly red-shifted populations of fucoxanthin are present. Tuning carotenoids to absorb in the green-yellow region of the visible spectrum appears to be a common evolutionary response to competition with other photosynthetic species in the aquatic environment.
Keywords: chlorofyl; xanthofyly; transportní proteiny; Carrier Proteins; světlosběrné proteinové komplexy; Chlorophyll; Carotenoids; Xanthophylls; karotenoidy; Spectrum Analysis, Raman; Ramanova spektroskopie; Light-Harvesting Protein Complexes